Fabricating Surfaces with Tunable Wettability and Adhesion by Ionic Liquids in a Wide Range. Issue 15 (19th November 2014) - Liu, Hongliang; Ding, Yi; Ao, Zhuo; Zhou, Yahong; Wang, Shutao; Jiang, Lei
<x xml:space="preserve">Abstract</x> A series of surfaces that can either be fully wetted or non‐wetted by three kinds of ionic liquids (ILs) are successfully designed by rationally controlling surface chemistries and structures. Meanwhile, the adhesion forces between these surfaces and the ILs can also be effectively modulated in a wide range. This fundamental research will greatly promote the development of IL‐based materials in practical applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>